2018 AIAA Aerospace Sciences Meeting 2018
DOI: 10.2514/6.2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic Validation of Installed Low Noise Propulsion for NASA’s N+2 Supersonic Airliner

Abstract: An aeroacoustic test was conducted at NASA Glenn Research Center on an integrated propulsion system designed to meet noise regulations of ICAO Chapter 4 with 10EPNdB cumulative margin. The test had two objectives: to demonstrate that the design meets the noise goal and to validate the noise prediction tools used during the design process. Variations in the propulsion system design and its installation were tested and the results compared against predictions. Far-field microphones measured the acoustic spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The flight stream was M∞= 0.3 for all test points. The data were transformed to M∞= 0.38 using procedures documented in previous tests 3 for EPNL analysis.…”
Section: Flow Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flight stream was M∞= 0.3 for all test points. The data were transformed to M∞= 0.38 using procedures documented in previous tests 3 for EPNL analysis.…”
Section: Flow Conditionsmentioning
confidence: 99%
“…NASA has been studying the viability of civilian supersonic airliners for some time 1,2 . In recent testing 3 a greater acoustic effect was found from installation than from nozzle type for a given engine. In the concept vehicle studied, one engine (center) was mounted above the aft deck of the aircraft while two engines (outboard) were mounted below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous testing 1 , greater acoustic benefit was found from installation than any other technology for a given engine. A propulsion system mounted on the top of the aircraft had substantial (2-3EPNdB) shielding of jet mixing noise in the frequency range of peak human annoyance.…”
Section: Introductionmentioning
confidence: 96%
“…This has been shown to offer significant noise reduction from both the fan and the exhaust system 4 . Recent tests at NASA Glenn Research Center have indicated a 3-4 EPNdB benefit from top-mounted engine installation relative to an underwing configuration 5 . Combined with chevrons, top-mounted propulsion can shield the high-frequency sources close to the nozzle exit and lessen the penalty associated with enhanced mixing.…”
Section: Introductionmentioning
confidence: 99%